Investigation Of Social Policy Concepts in Basic Education 1, 2, 3 and 4th Grade Textbooks - Şahinkaya, Adem (Fırat University, 2023)
Social policy has an important role in the development and progress of states. Social policy, which is a part of the society, resorts to many remedial and solution-oriented practices in order to eliminate inequality, poverty, unfair income distribution and unemployment. Ensuring social welfare and peace is among the main objectives of social policy, in line with the contributions of the economy and the social structure in a remarkable position for states. Through social policy, many services such as social security, social insurance, social assistance, education, housing and employment are implemented. Social policy has an indispensable standard in order to create an order where a social structure in which solid foundations are established and the social justice is provided. In order to know and understand what the concept of social policy, which is at a very important level, is started to be taught, especially in the first steps of education, it will help to establish solid social grounds. People’s thoughts, ideas and behaviors are shaped within the framework of educational activities, especially at the basic education level, they are more effective. Country administrators, who make plans about how the society will behave in the future, are influenced by the terms in the educational materials. The aim of this study is to examine the extent to which the topics within the scope of social policy are included in the textbooks in the National Education curriculum. The study is important in that it indicates the necessity of starting social policy to be taught from the basic education level. In the study, in depth research method was used from qualitative research methods. The subject of the study includes the responsibilities of the individual towards himself and the society, meeting social needs and how much his expectations are given at the basic education level. As a result of the study, it was determined that the study of the content of textbooks and the need to work on teaching social policy concepts to individuals. In the study, while individual benevolence was prioritised in the content of textbooks, the concepts about the social policies of the state were not included in the content of education and training.

Sosyal politika, devletlerin gelişimi ve kalkınması noktasında önemli bir role sahip olmaktadır. Toplumun bir parçası olan sosyal politika, eşitsizliğin, yoksulluğun, adil olmayan gelir dağılımının ve işsizliğin ortadan kaldırılabilmesi için birçok iyileştirici ve çözüm odaklı uygulamalara başvurmaktadır. Toplumsal refahın ve huzurun sağlanması, temel amaçları arasında yer alan sosyal politika, ekonominin ve sosyal yapının gelişimine katkıları doğrultusunda devletler için dikkate değer bir konumda yer almaktadır. Sosyal politika vasıtasıyla sosyal güvenlik, sosyal sigorta, sosyal yardım, eğitim, barınma, istihdam gibi birçok hizmetler de uygulanmaktadır. Sağlam temellerin kurulduğu bir toplumsal yapının inşa edilip sosyal adaletin sağlandığı bir düzenin oluşturulması için sosyal politika göz ardı edilemez bir standarda sahip olmaktadır. Oldukça önemli bir düzeyde yer alan sosyal politika kavramının ne olduğunun bilinmesi ve anlaşılabilmesi için özellikle de eğitimin ilk basamaklarında öğretilmeye başlanılması sağlam toplumsal zeminlerin oluşturulmasına yardımcı olacaktır. İnsanların düşünceleri, fikirleri ve davranışları eğitim-öğretim faaliyetleri çerçevesinde şekillenir. Toplumun gelecekte nasıl davranış göstereceği konusunda planlama yapan ülke yöneticileri, eğitim-öğretim materyallerinin içeriğindeki terimler ile etki etmektedir. Bu çalışmanın amacı, Milli Eğitim müfredatındaki ders kitaplarında, sosyal politika kapsamındaki konularının ne düzeyde yer verildiğini incelemektir. Çalışma sosyal politikanın, temel eğitim düzeyinden öğretilmeye başlatılmasının gerekliliğini belirtmesi açısından önemli olmaktadır. Çalışmada nitel araştırma yöntemlerinden yazılı doküman incelemesi yöntemi kullanılmıştır. Çalışmanın konusunu, bireyin, kendisine ve topluma karşı sorumlulukları, sosyal ihtiyaçların karşılanması ve beklentilerinin temel eğitim düzeyinde ne kadar verildiğini içermektedir. Çalışmanın sonucunda, ders kitapları içeriklerinin değerlendirilmesi ile sosyal politika kavramlarının bireylere öğretilmesi konusunda çalışma yapılması gerekliliği belirlenmiştir. Çalışmada ders kitapları içeriklerinde bireysel yardımseverlik ön planda tutulurken devletin sosyal politikaları hakkındaki kavramlar eğitim-öğretim içeriğine dâhil edilmemiştir.
TEMEL EĞİTİM 1, 2, 3 ve 4. SINIF DERS KİTAPLARINDA SOSYAL POLİTİKA KAVRAMLARININ ARAŞTIRILMASI
Keywords: Economics of Education; Eğitim Ekonomisi